Pengaruh CR & DER Terhadap Laba Bersih Pada Bank OCBC Periode 2013 - 2023 - Septi Anggela; Tarisa Risnaya Faradila; Triyadi Triyadi (CV. ITTC INDONESIA, 2025)
This study aims to analyze the effect of Capital Ratio (CR) and Debt to Equity Ratio (DER) on net profit at Bank OCBC NISP for the period 2013 to 2023. The main issue raised is how these two financial ratios can influence the bank's net profit performance. The method used in this research is multiple linear regression analysis, with data taken from the annual financial statements of Bank OCBC NISP. The results show that CR has a positive and significant effect on net profit, while DER has a negative effect on net profit. These findings provide important insights for bank management in decision-making related to capital and debt management to improve financial performance.